Challenging myomectomy of large cervical fibroid - successful fertility outcome: a case report - Banu, Jesmine; Altarique, Mostafa M.; Sultana, Rebeka; Lasker, Nastaran; Munira, S. M.; Anwary, Shaheen A.; Islam, Ariful (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
The cervical fibroids are rare and large cervical fibroids are rarer. Removing large cervical fibroids when a patient desires future fertility is a surgical challenge because of the risks of significant blood loss, bladder and ureteric injury, and unplanned hysterectomy. For women who desire future fertility, myomectomy can improve the chances of pregnancy by restoring normal anatomy. In this article, we describe a successful pregnancy following the restoration of the normal anatomy of the cervix by a challenging myomectomy in a sub-fertile patient with a large cervical fibroid. A 38-year-old nulliparous lady presented to the reproductive endocrinology and infertility (REI) department of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh with primary sub-fertility for five and half years, and dysmenorrhea for 2 years. She was a regularly menstruating woman with average flow and duration. Being a resident of Canada, she was diagnosed there as a case of large cervical fibroid (10×9 cm) by TVS extending up to the posterior wall of the uterus, cervix, and upper vagina impacted in the pouch of Douglas during infertility workup. For this reason, she was advised for in vitro fertilization (IVF) keeping the fibroid in situ. However, due to the failure of embryo transfer with this large cervical fibroid, she was advised for embryo transfer following myomectomy. Hysteroscopic myomectomy was tried first (in February 2019 in Canada) but was unable to be removed. Then Laparotomy was tried (in September 2019 in Canada) but failed again. Being a complicated case, she was counselled there for myomectomy by a multidisciplinary approach with the high risk of injury to the urinary bladder, ureter, bowel, and other pelvic structures. But she refused to do a myomectomy there after knowing the dreadful complications with the fear of injury to the pelvic organs. With this problem, she went to different institutions both in the country and abroad but couldn’t get the proper treatment. Finally, she visited the outpatient department (OPD) of the REI department, BSMMU, Dhaka, Bangladesh with the hope of getting the most appropriate treatment for her and she was reassured, counselled, and managed by a challenging myomectomy (in March 2022) through a combined approach of the vagina and abdominal route without any significant intra and post-operative complications. Her whole post-operative period was uneventful, the anatomy of the cervix was restored and detected by TVS, and trial transfer was done before embryo transfer with easy negotiation to the cervix. Finally, she conceived 1 year after myomectomy with easy frozen embryo transfer. Myomectomy in expert hand even for the large cervical fibroid can restore normal anatomy and can achieve successful pregnancy outcomes.